ESTIMASI KEPADATAN ORANGUTAN SUMATERA (Pongo abelii Lesson, 1827) BERDASARKAN JUMLAH SARANG DI PERBATASAN CAGAR ALAM DOLOK SIBUAL BUALI - Ferry Aulia Hawari; Pindi Patana; Erni Jumilaty (Program studi Kehutanan USU, 2015)
habitat is fragmented into several regions led to the survival of a population of a species depends on habitat conditions. The purpose of this study was to determine the population density of orangutans based on the number of nests in the Bulumario Village, Nature Reserve area Dolok Sibual Buali, District Sipirok, South Tapanuli, North Sumatra Province also determine the types of dominant vegetation is used as a nesting tree of the Sumatran orangutan in the village Bulumario, Knowing the value and Importance Value Index (IVI) of trees located in the village of Bulumario. This study was conducted in May 2014 until June 2014 in Nature Reserve Dolok Sibual Buali, Bulumario Village, District Sipirok, South Tapanuli, North Sumatra Province The results of this study indicate orangutan population density based on the number of nests in the Bulumario village and district CADS is 0,023 individuals/km2 or 2,332 individuals/ha of the total number of nests found 49 nests. Most nests were found at a distance of 0-100 meters of the entire track the number of 14 nests (28,57%) and the class that dominates nest class D is the number of 23 nests (46,94%). Dominant position of the nest is in a position which is a position I nest close to the main stem of the tree with the nest number 24 (48,98%). Generally the nest is found at an altitude of 6-10 meters with a sum of 15 nests (30,61%). Important Value Index (IVI) is highest on the type Hoteng (Quercus gamelliflora Blume.) Of the family Fagaceae with IVI 33,83%, and the Moraceae family that is dominated by the number seven species.Keywords: Sumatran Orangutan, Orangutan Density, nest, Important Value Index